2020
DOI: 10.4067/s0717-95022020000100069
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Morphometric Evaluation of the Wormian Bones

Abstract: Wormian (sutural) bones are accessory small bones located on the skull. These bones consist of extra ossification centers around cranial sutures. This study was carried out in 28 dry human skulls with unknown age and sex in the Department of Anatomy, Cukurova University. The aim of the study was to investigate incidence and to determine morphologic and morphometric characteristics of wormian (sutural) bones. Total incidence of wormian bone presence was 42.86 % (n=12) and most of them were located on lambdoid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…While that study did not report the average size of the Wormian bones, other studies, including anthropological assessments of dry skulls have reported an average size of 1.2 × 1.1 cm. 6 The patient we report had a Wormian bone that was much larger, at 4 × 2.8 cm—sizeable enough to cause appreciable contour anomaly at birth. There are few reports of such sizeable Wormian bones, and the existing reports describe large Wormian bones in the anterior fontanelle rather than lambdoid suture.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…While that study did not report the average size of the Wormian bones, other studies, including anthropological assessments of dry skulls have reported an average size of 1.2 × 1.1 cm. 6 The patient we report had a Wormian bone that was much larger, at 4 × 2.8 cm—sizeable enough to cause appreciable contour anomaly at birth. There are few reports of such sizeable Wormian bones, and the existing reports describe large Wormian bones in the anterior fontanelle rather than lambdoid suture.…”
Section: Discussionmentioning
confidence: 74%
“…4 On average, accessory bones typically measure approximately one square centimeter, though they can range from a few millimeters to several centimeters. 6 These ancillary bones can be associated with osteogenesis imperfecta as well as other disorders involving bone growth such as rickets, cleidocranial dysostosis, congenital hypothyroidism, and craniosynostosis. 4,7,8 In anthropologic studies of skulls, Wormian bones have also been documented to occur with increased prevalence in cultures employing intentional cranial deformation.…”
Section: Introductionmentioning
confidence: 99%
“…5). Most wormian bones occur in the lambdoidal suture or at lambda and less often in the occipitomastoid (Safak et al 2020) and coronal sutures (Bellary et al 2013). Some studies report an absence of sagittal sutural bones (Safak et al 2020) whereas others demonstrate its presence albeit in small numbers (Vijay et al 2017).…”
Section: Wormian Bonesmentioning
confidence: 99%
“…Wormian bones or sutural bones are accessory small bones which occur accidentally or intercalated between or near cranial sutures isolated from normal ossification center of skull [7].…”
mentioning
confidence: 99%
“…According to the literature, additional bones of the human skull with various localization in different populations occur with a frequency of 20-67% [2,6,7,11]. Some authors note gender differences in the frequency of inconstant cranial bones, while other authors don`t note such differences.…”
mentioning
confidence: 99%